ANALISIS KUALIFIKASI GURU PERSPEKTIF UNDANG-UNDANG NOMOR 14 TAHUN 2005 DAN SIYASAH DUSTURIYAH DI MADRASAH TSANAWIYAH MA’HAD AL-ZAYTUN - Asyifa, Nur; Taufiqurachman; Ngainnur Rohmah, Siti (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
Education is an important investment for countries, especially developing countries like Indonesia. Law no. 14 of 2005 describes the qualifications, competencies and ethical standards required for educators. Although professionalism among educators is essential, many lack an understanding of effective teaching strategies and methodologies, highlighting gaps in the education system that need to be addressed to improve the quality of teaching. This research examines teacher qualifications at Madrasah Tsanawiyah Ma'had Al-Zaytun, with a focus on the implications of Law Number 14 of 2005 and Siyasah Dusturiyah. Using qualitative research methods, researchers conducted field research, using techniques such as observation, interviews, and documentation to gather insights from experts and individuals directly involved in the educational context. Analysis of teacher qualifications at Madrasah Tsanawiyah Ma'had Al-Zaytun shows that teacher qualifications are in accordance with Law Number 14 of 2005 concerning teachers and lecturers. Teachers have strong personality competencies, demonstrating not only pedagogical knowledge and skills but also high moral values. Key traits include exemplary behavior, professionalism, patience, and empathy, highlighting the overall quality of educators at Ma'had Al-Zaytun. Keywords: Teacher Qualifications; Law 14 of 2005; Dusturiyah siyasah; Tsanawiyah Madrasah; Ma'had Al-Zaytun.